2010
DOI: 10.3354/meps08782
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching of an intertidal coralline alga: untangling the effects of light, temperature, and desiccation

Abstract: Intertidal macroalgae must tolerate temperature, light, and desiccation stresses when the tide recedes, and differences in physiological tolerance to these environmental stresses contribute directly to zonation patterns and community structure along the shore. When low tides occur on particularly hot sunny days, seaweeds may sustain physiological damage, lose pigment, and 'bleach.' Because bleaching events often occur when temperature, light, and desiccation stresses coincide, their precise cause is not unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 65 publications
4
53
1
3
Order By: Relevance
“…This supports the results of Martone et al. (), who found that desiccation was the primary environmental stress that limited the habitat range of intertidal Calliarthron . It is likely that intertidal Calliarthron is relegated to tidepools to avoid desiccation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This supports the results of Martone et al. (), who found that desiccation was the primary environmental stress that limited the habitat range of intertidal Calliarthron . It is likely that intertidal Calliarthron is relegated to tidepools to avoid desiccation.…”
Section: Discussionsupporting
confidence: 92%
“…Calliarthron , on the other hand, is abundant subtidally (Konar and Foster ) suggesting that it is well‐adapted to low light, cooler water temperatures, and is highly susceptible to desiccation (Padilla , Martone et al. ), although it can be found in some intertidal tidepools.…”
mentioning
confidence: 99%
“…Also, freezing is an important stress for polar and cold-temperate intertidal algal communities (Pearson et al 2000). Tolerance ranges (i.e., the range between upper and lower lethal temperatures) have been found to be broader in intertidal seaweeds occupying the upper shore than in species from the subtidal (Einav et al 1995;Stengel and Dring 1997;Martone et al 2010). Short-term thermal stress on the organism level seems ecologically less relevant for seaweeds growing in the subtidal where algae are virtually always submerged.…”
Section: Disruptive Temperature Stress and Thermal Tolerancementioning
confidence: 99%
“…As this species is generally found in intertidal brackish ponds (McLachlan and Bird 1986;Wang et al 2014), which is a very unstable environment susceptible to salt, temperature, and tidal oscillations (Abe et al 2001;Ji and Tanaka 2002;Shafer et al 2007;Martone et al 2010), even a mild drought tolerance is advantageous. G. tenuistipitata is more drought-tolerant than other species in the genus, such as G. corticata (Kumar et al 2011) and G. tikvahiae (Hodgson 1984), but not as tolerant compared The efficiency was measured as the quantity of good RNA extract per milligram of fresh tissue per time that each method lasted.…”
Section: Discussionmentioning
confidence: 99%